2006
DOI: 10.1002/rra.964
|View full text |Cite
|
Sign up to set email alerts
|

Selection of river flow indices for the assessment of hydroecological change

Abstract: • This is the pre-peer reviewed version of the article, which has been pub- Author for Correspondence:Wendy Monk, Canadian Rivers Institute, Department of Biology, Bag Service #45111, University of New Brunswick, Fredericton, New Brunswick, E3B 6E1, Canada. an 11-year macroinvertebrate community dataset (i.e. LIFE scores). The same 'best' models are produced using the PCA-based method and all 201 hydrological variables for two of the three river flow regime groups. However, weaker models are yielded by the PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 27 publications
(43 reference statements)
2
97
0
Order By: Relevance
“…Examination of the long-term LIFE scores for rivers at the national scale clearly indicated that the inter-annual pattern (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) closely tracked, or corresponded with, the 'most significant hydrological descriptor' (lnSMED = specific median discharge; Figure 4a and Figure 5a) identified from 201 flow descriptors (Monk et al, 2006;Monk et al, 2007b;Olden and Poff, 2003). This flow index provides an annual measure of river flow (discharge) scaled by catchment area.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Examination of the long-term LIFE scores for rivers at the national scale clearly indicated that the inter-annual pattern (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) closely tracked, or corresponded with, the 'most significant hydrological descriptor' (lnSMED = specific median discharge; Figure 4a and Figure 5a) identified from 201 flow descriptors (Monk et al, 2006;Monk et al, 2007b;Olden and Poff, 2003). This flow index provides an annual measure of river flow (discharge) scaled by catchment area.…”
Section: Discussionmentioning
confidence: 96%
“…Redundancy methods have been suggested as a means of reducing the range of hydrological predictors of ecological response. However such an approach may overlook more subtle ecological associations (Monk et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Between the 1956 and 1976 images (pre-regulation and hydropower operation), river flows were divided into two sub-periods. For 1956For -1967 Eleven hydrological indices, which are relevant for the river ecosystem (Olden and Poff, 2003;Mathews and Richter, 2007;Monk et al, 2007), were estimated from the flow record. The selected indices were a sub-set of those described by Belmar et al (2011) to characterize Mediterranean rivers whilst avoiding redundancy.…”
Section: River Flow Estimation and Characterization At The Study Sitesmentioning
confidence: 99%
“…Olden and Poff, 2003;Mathews and Richter, 2007;Monk et al, 2007;Belmar et al, 2011), and we evaluated 11 of these during our study (Table 4). Although our estimates of many of these indices were probably adversely affected by the low (monthly) resolution of the river flow time series, all of the indices show distinct changes over six decades and clearly correspond to the timing as well as the impacts of dam closure on the flow regime of the Mijares River.…”
Section: Temporal and Spatial Changes: The Utility Of Indices And Metmentioning
confidence: 99%